2022
DOI: 10.1146/annurev-orgpsych-012420-083120
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Interests in the Twenty-First-Century Workforce: Building on a Century of Interest Measurement

Abstract: Recent research has re-emphasized the importance of vocational interests for understanding workplace attitudes and behavior. As a result, there is a renewed interest in the assessment of vocational interests in organizations. Numerous interest assessments have been developed over the past century, and they are now administered to millions of people throughout the world. Nevertheless, there is still work to be done, particularly as interest assessments are increasingly being used in organizational settings. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Namely, Jones et al, (2021aJones et al, ( , 2021b found that group differences in interests have decreased over the decades (Jones et al, 2021a), and are small compared to other predictors (e.g., cognitive ability). If used for selection, they have the potential to mitigate concerns over adverse impact (Jones et al, 2021b), making them an important selection consideration for practitioners (Nye, 2022). Despite this, there has been very little attention granted to the use of interest inventories as a selection device (Iliescu et al, 2015;Nye et al, 2012Nye et al, , 2017Ryan et al, 1999;Van Iddekinge et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, Jones et al, (2021aJones et al, ( , 2021b found that group differences in interests have decreased over the decades (Jones et al, 2021a), and are small compared to other predictors (e.g., cognitive ability). If used for selection, they have the potential to mitigate concerns over adverse impact (Jones et al, 2021b), making them an important selection consideration for practitioners (Nye, 2022). Despite this, there has been very little attention granted to the use of interest inventories as a selection device (Iliescu et al, 2015;Nye et al, 2012Nye et al, , 2017Ryan et al, 1999;Van Iddekinge et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As with other noncognitive assessments, the high-stakes nature of the hiring process presents several unique challenges. This is particularly important for interest assessments given that most existing interest measures were developed for low-stakes career counseling or vocational purposes (Nye, 2022). In other words, many of the most popular existing interest inventories were not developed with the unique characteristics of the selection process in mind.…”
Section: Assessing Vocational Interests In High-stakes Selection Cont...mentioning
confidence: 99%
“…For example, Sackett and Ellingson (1997) showed that weighting conscientiousness and cognitive ability equally, rather than putting a higher weight on assessments such as the GRE, can dramatically reduce subgroup differences. Moreover, combining these predictors will not only reduce the race differences that would be observed with use of the GRE alone but also mitigate the observed differences between men and women on vocational interest measures (Nye, 2022). Likewise, recent work on pareto-optimization provides another approach to combining predictors (De Corte et al, 2007; Song et al, 2017), but a detailed discussion of this approach is beyond the scope of this commentary.…”
Section: Combining Predictorsmentioning
confidence: 99%